(untitled) (LEARNing Landscapes, 2018)
In this interview, professor and researcher Anne Bamford describes how she initially became interested in virtual learning via cyberbullying, particularly how image manipulation affects young people’s perceptions. Next, she discusses her European-wide study on “active 3D” in the classroom, which showed that the more control children took for their own learning, the better the results were. She argues that student involvement and engagement in implementing new technologies is critical for successful virtual learning in schools. Finally, she urges educators to “use the technology where it’s going to have the most impact” and not to “put it just for the sake of putting it in the curriculum.”